Analisis Pengaruh Teknologi Modern Bagi Perkembangan Usaha Mikro Pandai Besi di Kecamatan Rumbio Jaya Kabupaten Kampar - Zulfan Asadi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
The problems in this research are how is the development of a blacksmith micro business as well as what are the factors that influence the development of a blacksmith business and how the Sharia Economy views on the development of a blacksmith business in Rumbio Jaya District of Kampar Regency. This research is a field research, and the background of this study is the results of observations of the researcher on and interviews with informants. Thus, the data obtained in this study provide sufficient evidence. In blacksmith business, there are 30 entrepreneurs who are still active, this business is classified as a micro-businesses which have contributed to meet the needs of the agricultural and plantation communities and to improve the economy in Rumbio Jaya District of Kampar Regency as a livelihood and work field for the local workforce.Data sources were obtained directly in the field from informants by observation, interview, and documentation techniques. The population of this study are entrepreneurs and blacksmith craftsmen in Rumbio Jaya District of Kampar Regency. The findings of this study are that the development of a blacksmith's business in Rumbio Jaya District of Kampar Regency is quite good in terms of capital, marketing, raw materials and production results. The government has contributed to the development of this blacksmith micro business by organizing training for the workforce and also donating 2 units of forging machines each year. Furthermore, the blacksmith entrepreneurs also established a credit union and cooperated with PTPN V with a contract value of 1.6 M. The businessmen of the blacksmith craftsmen still survive from a hereditary heritage to the present with both technological and traditional equipments.